PENEBARAN IKAN UNTUK PELESTARIAN SUMBERDAYA PERIKANAN [Fish Restocking fo Sustaining Fisheries Resources] - Lenny S. Syafei (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2005)
Fisheries resources in inland waters have decreased. One tool to make fisheries resources to be sustained is reestocking. This paper discusses the goals of fish restocking and failure and the steps of restocking into the waters.